DETERMINANTS OF TAX COMPLIANCE IN TRADITIONAL TEXTILE ENTERPRISES - Rochmad Bayu Utomo; Dina Karista; I Gusti Ayu Made Agung Mas Andiani Pratiwi; Ni Luh Gde Ana Pertiwi (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2026)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) is crucial to strengthening national fiscal capacity and supporting creative economies rooted in cultural heritage. Despite their significant economic contributions, traditional textile artisans in tourism-based villages often fall short in meeting tax obligations. This study explores how taxpayer awareness, knowledge, digital financial tools, and the quality of tax administration influence compliance behavior, with tax payment motivation examined as a mediating variable among MSMEs in Java and Bali. Utilizing a quantitative approach, data were collected via Likert-scale surveys and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that taxpayer knowledge, awareness, digital banking access, and service quality positively impact tax payment motivation. These factors, along with motivation, also contribute significantly to improved compliance. Tax payment motivation bridges internal and external drivers, reinforcing compliant behavior. The findings highlight the importance of implementing targeted tax education, enhancing service delivery, and expanding digital banking infrastructure to promote tax compliance and support the growth of culturally driven MSMEs.